Prevalence of glucose tolerance test abnormalities in women with polycystic ovarian syndrome - Gracelyn, Leila J.; Pushpagiri, Niroopama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: PCOS is the most frequent endocrine disorder, often complicated by chronic anovulatory infertility and hyperandrogenism. High prevalence of impaired glucose tolerance and type 2 diabetes is observed due to peripheral insulin resistance. Holistic approach to the disorder to prevent long-term complications is required. The objective of the study was to study the prevalence of oral glucose tolerance test abnormalities (OGTT) in PCOS women and to study the significance of risk factors contributing to glucose intolerance in women with PCOS. Methods: Hospital based analytical cross sectional study was conducted for 1 and ½ years among 200 women with PCOS. Women diagnosed as PCOS according to Rotterdam’s criteria. Women with other causes of anovulation, premature ovarian failure and women already diagnosed to be diabetic. Results: Abnormal glucose tolerance was observed in 32 (16 %) of the 200 PCOS women. Among them 14.5% had impaired glucose tolerance (IGT) and 1.5% had diabetes. There was a significant trend towards increasing prevalence of IGT and diabetes in females with higher BMI, waist circumference, clinical and biochemical hyperandrogenism and patients with metabolic syndrome. Conclusions: High prevalence of IGT and Non-Insulin Dependent Diabetes Mellitus (NIDDM) in women with PCOS was observed than expected. They have accelerated conversion from IGT to NIDDM. IGT is often asymptomatic and is a known risk factor for type 2 DM and cardiovascular disease. OGTT with 75 gms of glucose is the best screening method for glucose intolerance and a good measure to diagnose type 2 DM in PCOS women.